2010
DOI: 10.1016/j.yhbeh.2009.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Food supplementation and testosterone interact to influence reproductive behavior and immune function in Sceloporus graciosus

Abstract: The energetic resources in an organism's environment are essential for executing a wide range of life history functions, including immunity and reproduction. Most energetic budgets, however, are limited, which can lead to trade-offs among competing functions. Increasing reproductive effort tends to decrease immunity in many cases; and increasing total energy via supplemental feedings can eliminate this effect. Testosterone (T), an important regulator of reproduction, and food availability are thus both potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 61 publications
1
57
0
2
Order By: Relevance
“…Although the majority of studies have shown an inhibitory effect of T on the immune system, several studies have shown the opposite effect (Tschirren et al 2005). For example, in barn swallows, Saino et al (1995) demonstrated that while T was positively related to ectoparasite load, antibody levels, and number of eosinophils actually increased with experimentally elevated T. In another lizard species, T appeared to enhance the immune response and reproductive capacity during periods of high food availability, but when resources were limited, T inhibited the immune response (Ruiz et al 2010). In our study, lizards were provided with ad libitum food for 2 weeks while implants took effect, raising the possibility that the combination of high food availability and increased T concentrations possibly improved their immune response to ectoparasites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of studies have shown an inhibitory effect of T on the immune system, several studies have shown the opposite effect (Tschirren et al 2005). For example, in barn swallows, Saino et al (1995) demonstrated that while T was positively related to ectoparasite load, antibody levels, and number of eosinophils actually increased with experimentally elevated T. In another lizard species, T appeared to enhance the immune response and reproductive capacity during periods of high food availability, but when resources were limited, T inhibited the immune response (Ruiz et al 2010). In our study, lizards were provided with ad libitum food for 2 weeks while implants took effect, raising the possibility that the combination of high food availability and increased T concentrations possibly improved their immune response to ectoparasites.…”
Section: Discussionmentioning
confidence: 99%
“…All female lizards with artificiallyinduced vitellogenesis in our study were fed ad libitum for three weeks prior to infestation with ticks, which may have improved their nutritional status to the point where the energetic costs of vitellogenesis did not have negative impacts on their immune response to the ticks. To confirm this, as well as the hypothesis that energetic state modulates a T-induced alteration of immune function in males that then affects tick feeding duration, experimental manipulation of vitellogenesis and T concentrations must be paired with controlled manipulation of food availability as in French et al (2007a, b, c) and Ruiz et al (2010Ruiz et al ( , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Immune function is often modulated by current environmental conditions and physiological state, including reproductive condition (French et al, 2007), hormone levels (Flatt et al, 2008), nutrient availability (Cotter et al, 2011) and their interaction (Ruiz et al, 2010;Cohen et al, 2012). However, immune function can also be shaped by conditions experienced during development (Galic et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de a elevação de parâmetros imunológicos por testosterona ser raramente reportada em animais de laboratório e humanos, a imunossupressão não é uma condição obrigatória. Maior imunocompetência associada a níveis elevados de testosterona em condições naturais (Ezenwa et al, 2012; Madelaire, dados não publicados) e após aplicação experimental (Roberts & Peters, 2009;Ruiz et al, 2010;Desprat et al, 2015) foram encontrados em alguns vertebrados, associado a fatores como condição corpórea, alimentação, dominância no grupo, estágio de vida e parâmetro imunológico considerado. Um estudo realizado com hamsters, entretanto, reportou aumento de imunidade mediada por célula também in vitro (Bilbo & Nelson, 2001), sugerindo que a testosterona pode ter efeitos diretos no aumento da imunocompetência em determinadas situações.…”
Section: Comportamento Vocal Hormônios Esteroides E Imunidadeunclassified